Evaluation of Patients with Organizing Pneumonia in the Post-COVİD-19 Period - Kazancı, Ülkü; Balın, Şafak Özer (My University, 2022)
Objective: This study aimed to retrospectively evaluate the cases of healthy adults, diagnosed with histologically confirmed organizing pneumonia and had shortness of breath and fatigue persist for at least three months in the post-COVID-19 period. Materials and Methods: Seventeen patients admitted to our hospital with shortness of breath and fatigue complaints between September 2020 and May 2021 were diagnosed with SARS-CoV-2 infection at least three months before the last admission and diagnosed with organizing pneumonia confirmed both radiologically and pathologically were included. Results: All of the patients were previously hospitalized due to COVID-19. The median time elapsed between the diagnosis of COVID-19 and recurrent hospitalization due to organizing pneumonia was four months. Our patients had bilateral lobular; subpleural densities vary from ground glass to the middle/lower lung consolidation, which is the typical radiological feature of organizing pneumonia. Partial lobular excision of the lung was performed in all patients. İntra alveolar exudate, characterized by granulation tissue and fibroblast proliferation in the lung parenchyma, was detected in all patients. Conclusion: We believe that secondary organizing pneumonia should be considered among patients with COVID-19 pneumonia, especially in the case of persistent or recurrent respiratory symptoms and ongoing lung infiltrates. Thus, it will be possible to provide the proper medical approaches instead of unnecessary surgical intervention.
Keywords: Solunum Sistemi; Patoloji